Rational design and synthesis of degradable poly(imidazolium ester) antibiotics - Xu, Xiaofei (Nanyang Technological University, 2024)
The essential quest for innovative medications to address drug-resistant bacterial infections carries immense importance, owing to the widespread emergence of bacterial resistance against traditional antibiotics. While antimicrobial polymers have been explored as promising substitutes for antibiotics in academic scenarios, a majority of these polymers feature non-degradable backbones. However, this characteristic gives rise to concerns about the potential for prolonged accumulation in both clinical environments and the natural surroundings. Moreover, the progression of antimicrobial polymers to in vivo trials has been limited, primarily due to the obstacles encountered in achieving effective therapeutic selectivity. In this study, we embarked on the design and synthesis of a diverse range of polymers known as poly(imidazolium ester)s (PIEs), featuring ester and imidazolium functional groups in the polymer backbone. This innovative approach introduced a new category of degradable antimicrobial polymers. Our investigation into the relationship between polymer structure and activity unveiled crucial insights into the factors influencing both degradability and antimicrobial effectiveness. Through systematic experimentation, we established a library of degradable antimicrobial polymers possessing antibiotic-like potency and tunable degradation rates. Systematic evaluation, assessing bacterial potency and toxicity, unveiled a standout candidate, PBIE3. This compound showcased an unparalleled therapeutic selectivity, denoting its exceptional safety and efficacy profile. Notably, PBIE3 exhibited the remarkable ability to eliminate drug-resistant bacteria while mitigating the emergence of resistance. Mechanistic investigations revealed that PBIE3 exerts its antimicrobial effect by penetrating bacterial membranes and forming complexes with cytoplasmic DNA. This contrasts with the prevalent membrane-disruptive mode observed in most cationic antimicrobial polymers. Encouragingly, PBIE3 demonstrated both safety and efficacy across various infection models in mice, encompassing peritonitis, pneumonia, and thigh infections. Notably, it effectively eliminated both Gram-positive and Gram-negative multidrug-resistant strains in murine infections. This new class of non-toxic degradable antimicrobial polymers with exceptional in vivo performance holds promising potential for future clinical applications.